An Appraisal of Religious Fanaticism and the Imperative of the Dialogue of Life and Tolerance in Nigeria - Haaga, Paul T.; Ngbea, Gabriel T. (International Journal of Law and Society, 2023)
This paper argues that critical reflection on Nigeria's situation in the context of crisis and conflict reveals that religion ranks first as a cause of crisis and conflict. This paper seeks to engage in philosophical reflection on religious bigotry in Nigeria and ascertain how it affects our existence. The type of research used is qualitative with a descriptive approach. Primary data was obtained through in-depth interviews with respondents, while secondary data came from literature, case studies, previous research reports and related legal documents. Qualitative data analysis uses a thematic approach and data interpretation. The results of this study are on two fronts: the first front preoccupies itself with discourse on the scourge of religious fanaticism in Nigeria, while the second front reflects the fertility of life dialogue as a form of interreligious dialogue to withstand the threat of religious fanaticism with the aim of elevating a culture of religious tolerance that creates peaceful coexistence. necessary for sustainable development and progress in contemporary Nigeria.